User evaluation on curriculum design information system - Thong, Chee Ling; Jusoh, Yusmadi Yah; Abdullah, Rusli; Alwi, Nor Hayati (IEEE (IEEE Xplore), 2014)
In Information System development, users play an important role in providing input in the development process. This includes both user requirement gathering and evaluation phases. This paper presents the later which is the perception of curriculum designers who have tested the curriculum design information system during the evaluation phase and provide their feedback to further enhance the system. The work is conducted based on authors’ prior work. This paper focuses on user evaluation on the usefulness and ease of use of the curriculum design information system which is developed for curriculum designers in institution of higher learning.